Response to bronchodilator and clinical, pathophysiological features in patients with nonasthmatic eosinophilic bronchitis. (11th December 2019) - Lai, Kefang; Yi, Fang; Han, Lina; Liu, Baojuan; Zhang, Xu; Xue, Yongxin; Luo, Wei; Chen, Qiaoli
Abstract: Introduction: Whether nonasthmatic eosinophilic bronchitis (NAEB) shows response to bronchodilator (RB) remains unclear. Objectives: To investigate the RB and its relationship with clinical and pathophysiological features in NAEB. Methods: Fifty‐one patients with NAEB were assigned in a 2:1 ratio to receive oral bambuterol hydrochloride (n = 34, 10 mg, once daily, for 3 days) or matched placebo (n = 17) randomly, of whom 48 patients (32 with bronchodilator and 16 with placebo) completed the study. Sputum induction, spirometry and cough reflex sensitivity were measured. RB was considered when cough Visual analogue scale (VAS) score decreased 30% or more after treatment. Cough reflex sensitivity was defined as the lowest concentration of capsaicin inducing five coughings or more (C5), and presented as Log C5. Results: The responsive rate of patients with bronchodilator was significantly higher than that with placebo (34.4% vs 6.3%, P  < 0.05). The VAS score decreased significantly in patients with bronchodilator (median: 6.0‐3.0, P  < 0.01). There was a significantly higher median Log C5 (2.7 vs 1.3, P  < 0.05), and a higher trend of decline in FEV1 % predicted and MMEF% predicted after bronchial provocation in patients with RB as compared with patients without RB. No significant differences in baseline percentages of sputum eosinophil were found between patients with RB and that without RB. Conclusions: One third of patients with NAEB respond well to bronchodilator treatment, which are related with lower cough reflex sensitivity and increased airway responsiveness. The relationship between NAEB and asthma needs to be investigated further.